High-voltage lithium nickel manganese oxide cathode material with multi-stage interface passivation layer and preparation process thereof
By forming a multi-level interface passivation layer on the surface of LNMO, the positive electrode material of lithium-ion batteries, the problem that the existing modification methods cannot take into account both ion conduction and chemical stability is solved, the battery's conductivity, rate performance and cycle life are improved, and higher chemical stability and safety are achieved.
Patent Information
- Application Number
- CN202510621340.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-14
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-05-14
AI Technical Summary
Existing modification methods cannot simultaneously take into account the ion conductivity, chemical stability and surface interface stability of lithium-ion battery positive electrode materials, resulting in poor performance of the battery in high-performance applications.
A multi-level interface passivation layer design of Li3BO3-LiAlO2 composite layer, PAN-F conductive polymer layer and g-C3N4 quantum dot modification layer is adopted. Through in-situ electrochemical pre-activation and synergistic modification, a multi-level interface passivation layer is formed that is sequentially coated on the LNMO surface, which improves the lithium ion diffusion rate, blocks the electrolyte penetration and catalyzes the decomposition of by-products.
It significantly improves the conductivity, rate performance and cycle life of lithium-ion batteries, reduces transition metal dissolution and oxygen vacancy concentration, and enhances the chemical stability and safety of the material.
Smart Images

Figure CN120184224B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of lithium batteries, in particular to a high-voltage lithium nickel manganese oxide positive electrode material with a multi-stage interface passivation layer and a preparation process thereof. BACKGROUND
[0002] Lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4, abbreviated as LNMO) is a kind of spinel high-voltage positive electrode material, which has attracted much attention due to its high energy density, low cost and good cycle stability. The theoretical discharge specific capacity of LNMO can reach 146.7 mAh / g, the voltage platform is as high as 4.7 V, and the energy density can reach 650 Wh / kg, which has wide application prospects in consumer electronics, electric vehicles and energy storage equipment.
[0003] The spinel structure of LNMO endows it with excellent rate performance and structural stability, and at the same time, due to the absence of cobalt element, its production cost is relatively low, and it is environmentally friendly, which is one of the important positive electrode materials for the next generation of high-energy density lithium-ion batteries.
[0004] Although LNMO has many advantages, its performance still needs to be further optimized to meet the higher standard of battery requirements. The current LNMO modification methods and problems are as follows:
[0005] (1) Single-layer coating (such as LiF): unable to balance ion conduction and chemical stability
[0006] Single-layer coating modification strategies, such as coating with LiF, can improve material performance in some aspects, but have obvious limitations. LiF is a typical inorganic compound with high chemical and thermal stability, which can protect the surface of the positive electrode material to a certain extent and prevent it from reacting with the electrolyte. However, the ionic conductivity of LiF is relatively low, which will hinder the rapid transport of lithium ions between the electrode and the electrolyte, thereby affecting the rate performance of the battery.
[0007] In addition, the single-layer coating structure often cannot form an effective ion conduction network. Due to the limited ion conduction ability of LiF, it may become a bottleneck for lithium ion migration, especially at high current density, which will increase the polarization of the battery and reduce its energy efficiency. More importantly, the single-layer coating layer may not completely cover the active surface of the positive electrode material, especially at the defect sites or grain boundaries of the material, and the electrolyte may still come into direct contact with the positive electrode material, causing side reactions and affecting the cycle stability and safety of the battery.
[0008] Therefore, although single-layer coating modification can improve the chemical stability of the positive electrode material to a certain extent, it cannot balance the ion conduction performance, which limits its application in high-performance lithium-ion batteries.
[0009] (2) Non-in-situ coating (such as mechanical mixing carbon layer): uneven coating, easy to peel off after cycling
[0010] Non-in-situ coating, such as introducing carbon layer by mechanical mixing method, is a relatively simple modification strategy. This method usually involves physically mixing carbon materials (such as graphite, carbon nanotubes, etc.) with the positive electrode material, and then sintering at high temperature to deposit a carbon layer on the surface of the positive electrode material. However, the coating effect of this method is often not ideal and has many problems.
[0011] Firstly, it is difficult to achieve uniform coating of carbon layer on the surface of positive electrode material by mechanical mixing method. Due to the different particle shapes, sizes and surface properties of positive electrode materials, the carbon layer may not uniformly cover each particle, resulting in lack of protection in some areas and over-coating in other areas. This uneven coating not only affects the interface stability between the positive electrode material and the electrolyte, but also may cause the diffusion path of lithium ions to be longer, reducing the rate performance of the battery.
[0012] Secondly, the bonding force between the non-in-situ coated carbon layer and the positive electrode material is usually weak. During the charge and discharge cycle of the battery, the positive electrode material will undergo volume change and structural stress, which may cause the interface between the carbon layer and the positive electrode material to separate, and even the carbon layer to peel off. Once the carbon layer peels off, the surface of the positive electrode material will be exposed to the electrolyte again, triggering side reactions, accelerating the decay of the battery, and reducing its cycle life and safety.
[0013] Therefore, although non-in-situ coating modification is simple to operate, it has the problems of uneven coating and easy peeling after cycling, which is difficult to meet the needs of high-performance lithium-ion batteries.
[0014] (3) Bulk doping (such as Ti 4+ ): cannot solve the surface interface problem, high temperature capacity decay > 30% Bulk doping is a method of modifying material performance by introducing heterovalent ions (such as Ti 4+ ) into the lattice of the positive electrode material. This method can to some extent regulate the structural stability and electrochemical performance of the positive electrode material. However, bulk doping also has obvious limitations, especially in solving the surface interface problem and high temperature capacity decay.
[0015] Firstly, bulk doping mainly acts on the bulk phase of the positive electrode material, and has limited effect on the modification of the material surface. The surface interface problems of the positive electrode material, such as electrolyte decomposition, side reactions, etc., mainly occur on the surface of the material, and bulk doping cannot effectively inhibit these surface reactions. Therefore, even if bulk doping can improve the bulk phase stability of the positive electrode material, it cannot completely solve the surface interface problem, which limits its role in improving the cycle stability and safety of the battery.
[0016] Secondly, the capacity decay problem of bulk-doped cathode materials is still serious when working at high temperature. Experiments show that the capacity decay rate of some bulk-doped cathode materials (such as Ti 4+ doped) may exceed 30% under high-temperature cycling conditions. This is mainly due to the decline in structural stability of the cathode material at high temperature and the intensification of surface interface reactions. Although bulk doping can improve the bulk stability of the material, it cannot effectively inhibit the surface side reactions at high temperature, resulting in poor cycle performance and capacity retention of the battery at high temperature.
[0017] Therefore, although bulk doping modification can improve the bulk stability of the cathode material to some extent, it cannot effectively solve the surface interface problem, and the capacity decay at high temperature is still serious, which limits its application in high-performance lithium-ion batteries.
[0018] In summary, the three modification methods of single-layer coating, non-in-situ coating and bulk doping each have their limitations, and further exploration and development of more effective modification strategies are needed to balance the ion conduction performance, chemical stability and surface interface stability of the cathode material, so as to meet the needs of high-performance lithium-ion batteries. SUMMARY
[0019] The technical problem to be solved by the present application is to overcome the shortcomings of the prior art and provide a high-voltage lithium nickel manganese oxide cathode material with a multi-level interface passivation layer and a preparation process thereof.
[0020] The technical scheme of the present application is as follows:
[0021] On the one hand, the present application provides a preparation process of a high-voltage lithium nickel manganese oxide cathode material with a multi-level interface passivation layer, comprising the following steps:
[0022] S1: In-situ construction of Li3BO3-LiAlO2 composite layer: immerse the LNMO precursor in a mixed solution of ethanol and water containing Al(NO3)3 and H3BO3, and stir; add ammonia water to adjust pH to 8.5-9.5, generate Al(OH)3-B(OH)3 coprecipitate, centrifuge and dry, then anneal to form
[0023] Li3BO3-LiAlO2 composite layer on the LNMO precursor;
[0024] S2: PAN-F conductive polymer layer deposition: place the material obtained in step S1 in a CVD reaction chamber, introduce a mixed gas of acrylonitrile (PAN) and NF3, and react at 400-500℃ for 1-3h to polymerize fluorinated polyacrylonitrile (PAN-F) on the surface of the material; then subject the obtained material to Ar plasma treatment;
[0025] S3: g-C3N4 quantum dot modification: disperse g-C3N4 quantum dots in an organic solvent, add a surfactant, and perform ultrasonic treatment; immerse the material obtained in step S2 in the above dispersion liquid, stir, centrifuge and dry to obtain a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer.
[0026] Preferably, in step S1, the D50 of the LNMO precursor is 200-300 nm.
[0027] Preferably, in step S1, in the mixed solution, the concentration of Al(NO3)3 is 0.2-0.4 mol / L, the concentration of H3BO3 is 0.1-0.2 mol / L, and the volume ratio of ethanol to water is (3-5):1; the molar ratio of the LNMO precursor, Al(NO3)3, and H3BO3 is 100:(2-4):(1-2).
[0028] Preferably, in step S1, the stirring temperature is 60-80℃, and the stirring time is 4-8h; the ammonia water dropping speed is 1-2mL / min.
[0029] Preferably, in step S1, the annealing temperature is 500-600℃, the heating rate is 2-5℃ / min, the annealing time is 3-6h, and the annealing is performed in an air atmosphere; the thickness of the Li3BO3-LiAlO2 composite layer formed is 6-8nm.
[0030] Preferably, in step S2, in the mixed gas, the volume ratio of acrylonitrile to NF3 is (10-15):1; the power of the Ar plasma treatment is 100-150W, and the time is 10-20min; the thickness of the PAN-F conductive polymer layer is 2-3nm.
[0031] Preferably, in step S3, the organic solvent is NMP, and the surfactant is CTAB.
[0032] Preferably, in step S3, the concentration of g-C3N4 quantum dots in the dispersion liquid is 0.5-1mg / mL, and the concentration of the surfactant is 0.1-0.3wt.%.
[0033] Preferably, in step S3, the ultrasonic treatment time is 30-60min; the stirring temperature is 60-80℃, and the stirring time is 6-8h.
[0034] In another aspect, the present application provides a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer prepared by the above preparation process.
[0035] Compared with the prior art, the present application has the following beneficial effects:
[0036] The high-voltage lithium nickel manganese oxide positive electrode material with a multistage interface passivation layer is prepared by a design of a multistage interface passivation layer and in-situ electrochemical pre-activation, and is sequentially coated with a Li3BO3-LiAlO2 composite layer, a PAN-F conductive polymer layer and a g-C3N4 quantum dot modification layer on the surface of the LNMO. The Li3BO3-LiAlO2 composite layer is generated in-situ by a sol-gel method, Li3BO3 fills the grain boundary cracks and improves the lithium ion diffusion rate, and LiAlO2 inhibits the generation of oxygen vacancies and reduces the surface oxygen vacancy concentration. The PAN-F conductive polymer layer forms a crosslinked network by chemical vapor deposition (CVD), blocks the penetration of electrolyte and anchors free Ni 2+ / Mn 2+ , so that the dissolution concentration is <1 ppm. In the g-C3N4 quantum dot modification layer, the ultra-thin carbon nitride (g-C3N4) quantum dots are modified on the surface by electrostatic self-assembly and catalyze the decomposition of electrolyte byproducts (such as ROCO2Li), thereby improving the electronic conductivity. BRIEF DESCRIPTION OF DRAWINGS
[0037] Figure 1 is a structural schematic diagram of the high-voltage lithium nickel manganese oxide positive electrode material with a multistage interface passivation layer of the present application.
[0038] Figure 2 is an SEM diagram of the high-voltage lithium nickel manganese oxide positive electrode material with a multistage interface passivation layer prepared in Example 1 of the present application.
[0039] Figure 3 is an EDS diagram of the high-voltage lithium nickel manganese oxide positive electrode material with a multistage interface passivation layer prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0040] In order for those skilled in the art to better understand the technical solutions in the present application, the technical solutions of the present application will be described clearly and completely below in combination with the embodiments of the present application.
[0041] Example 1
[0042] The preparation process of the high-voltage lithium nickel manganese oxide positive electrode material with a multistage interface passivation layer of the present embodiment includes the following steps:
[0043] S1: In-situ construction of the Li3BO3-LiAlO2 composite layer
[0044] 10 mol of LNMO precursor powder (D50 = 250 nm, specific surface area 5 m 2 / g) is immersed in 1000 mL of a mixed solution containing 0.2 mol / L of Al(NO3)3 and 0.1 mol / L of H3BO3 in ethanol and water (volume ratio of ethanol to water is 3:1), and is ultrasonically dispersed for 30 min at 300 W.
[0045] 60 °C constant temperature stirring for 4 h, ammonia water was added at a rate of 1 mL / min to adjust pH = 8.5, and Li3BO3-LiAlO2 composite layer was formed on the surface of LNMO precursor.
[0046] Al(OH)3-B(OH)3 co-precipitation, centrifugal drying, and then annealing at 500 °C for 3 h in air atmosphere (heating rate 2 °C / min), a 6 nm thick Li3BO3-LiAlO2 composite layer was formed on the LNMO precursor.
[0047] S2: PAN-F conductive polymer layer deposition
[0048] The material obtained in step S1 was placed in a CVD reaction chamber, and a mixed gas of PAN and NF3 (volume ratio of PAN to NF3 10:1, total flow rate 100 sccm) was introduced, and polymerization was carried out at 400 °C for 1 h under a pressure of 10 kPa, and a 2 nm thick fluorinated polyacrylonitrile (PAN-F) was formed on the surface of the material.
[0049] Subsequently, the obtained material was subjected to Ar plasma treatment (power 100 W, time 10 min), and the adhesion between the polymer layer and the substrate was enhanced (peeling force test > 5 N / cm 2 ).
[0050] S3: g-C3N4 quantum dot modification
[0051] Bulk g-C3N4 was ultrasonically exfoliated in concentrated H2SO4 for 6 h (power 500 W), and quantum dots with a particle size of <5 nm were obtained by centrifugation.
[0052] The g-C3N4 quantum dots were dispersed in NMP, and a surfactant CTAB was added, and ultrasonic treatment was carried out for 30 min, and in the obtained dispersion, the concentration of g-C3N4 quantum dots was 0.5 mg / mL, and the concentration of CTAB was 0.1 wt.%. The material obtained in step S2 was immersed in the above dispersion, and stirring was carried out at 80 °C for 6 h, and centrifugal drying was carried out, and a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer (structure as shown in Figure 1 ) was obtained, and was recorded as g-C3N4 quantum dot@PAN-F@Li3BO3-LiAlO2@LNMO (g-C3N4 quantum dot coverage > 95%, verified by SEM-EDS).
[0053] The SEM and EDS images of the lithium nickel manganese oxide positive electrode material prepared in this example are shown in Figures 2-3 From the SEM image, it can be seen that the material prepared retains the spinel structure of lithium nickel manganese oxide, and from the EDS image, it can be seen that the coating elements are uniformly covered.
[0054] Example 2
[0055] S1: In-situ construction of Li3BO3-LiAlO2 composite layer
[0056] 10 mol of LNMO precursor powder (D50 = 300 nm, specific surface area 5 m 2 / g) was immersed in 1000 mL of a mixed solution of ethanol and water containing 0.3 mol / L of Al(NO3)3 and 0.15 mol / L of H3BO3 (volume ratio of ethanol to water 4:1) and ultrasonically dispersed for 40 min at 350 W.
[0057] 70°C constant temperature stirring for 5 h, dropwise adding ammonia water to adjust pH = 9 at a rate of 1.5 mL / min, generating
[0058] Al(OH)3-B(OH)3 co-precipitation, centrifugal drying, and annealing at 550°C for 4 h in an air atmosphere (heating rate 4°C / min) to form a 7 nm Li3BO3-LiAlO2 composite layer on the LNMO precursor.
[0059] S2: PAN-F conductive polymer layer deposition
[0060] The material obtained in step S1 was placed in a CVD reaction chamber, and a mixed gas of PAN and NF3 (volume ratio of PAN to NF3 12:1, total flow rate 100 sccm) was introduced, and reacted at 450°C for 2 h, and the pressure was maintained at 10 kPa, and a 2.5 nm thick fluorinated polyacrylonitrile (PAN-F) was polymerized on the surface of the material.
[0061] Subsequently, the obtained material was subjected to Ar plasma treatment (power 120 W, time 15 min), and the adhesion of the polymer layer to the substrate was enhanced (peeling force test > 5 N / cm 2 ).
[0062] S3: g-C3N4 quantum dot modification
[0063] Bulk g-C3N4 was ultrasonically exfoliated in concentrated H2SO4 for 6 h (power 500 W), and quantum dots with a particle size < 5 nm were obtained by centrifugation.
[0064] The g-C3N4 quantum dots were dispersed in NMP, and a surfactant CTAB was added, and ultrasonically treated for 50 min, and in the obtained dispersion, the concentration of g-C3N4 quantum dots was 0.7 mg / mL, and the concentration of CTAB was 0.2 wt.%. The material obtained in step S2 was immersed in the above dispersion, and stirred at 70°C for 7 h, and centrifugally dried to obtain a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer, denoted as g-C3N4 quantum dot@PAN-F@Li3BO3-LiAlO2@LNMO
[0065] Example 3
[0066] S1: In-situ construction of Li3BO3-LiAlO2 composite layer
[0067] 10 mol of LNMO precursor powder (D50 = 200 nm, specific surface area 5 m 2 / g) was immersed in 1000 mL of a mixed solution of ethanol and water containing 0.4 mol / L of Al(NO3)3 and 0.2 mol / L of H3BO3 (volume ratio of ethanol to water 5:1) and ultrasonically dispersed for 50 min at 400 W.
[0068] 80°C constant temperature stirring for 8 h, ammonia water was added at a rate of 2 mL / min to adjust pH = 9.5, and 8 nm of Li3BO3-LiAlO2 composite layer was formed on the LNMO precursor.
[0069] Al(OH)3-B(OH)3 co-precipitation, centrifugal drying, and annealing at 600°C for 6 h in an air atmosphere (heating rate 5°C / min) to form an 8 nm Li3BO3-LiAlO2 composite layer on the LNMO precursor.
[0070] S2: PAN-F conductive polymer layer deposition
[0071] The material obtained in step S1 was placed in a CVD reaction chamber, and a mixed gas of PAN and NF3 (volume ratio of PAN to NF3 15:1, total flow rate 100 sccm) was introduced, and polymerization was carried out at 500°C for 3 h under a pressure of 10 kPa to form a 3 nm thick fluorinated polyacrylonitrile (PAN-F) on the surface of the material.
[0072] Subsequently, Ar plasma treatment was performed on the obtained material (power 150 W, time 20 min) to enhance the adhesion of the polymer layer to the substrate (peeling force test > 5 N / cm 2 ).
[0073] S3: g-C3N4 quantum dot modification
[0074] Bulk g-C3N4 was ultrasonically exfoliated in concentrated H2SO4 for 6 h (power 500 W), and quantum dots with a particle size < 5 nm were obtained by centrifugation.
[0075] The g-C3N4 quantum dots were dispersed in NMP, and a surfactant CTAB was added, and ultrasonic treatment was performed for 60 min. In the obtained dispersion, the concentration of g-C3N4 quantum dots was 1 mg / mL, and the concentration of CTAB was 0.3 wt.%. The material obtained in step S2 was immersed in the above dispersion, stirred at 60°C for 8 h, and dried by centrifugation to obtain a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer, denoted as g-C3N4 quantum dot@PAN-F@Li3BO3-LiAlO2@LNMO.
[0076] Comparative Example 1
[0077] The difference from Example 1 is that the nickel lithium manganate cathode material of Comparative Example 1 is LNMO, and no modification treatment of steps S1-S3 is performed.
[0078] Comparative Example 2
[0079] The difference from Example 1 is that steps S2-S3 are not performed.
[0080] Comparative Example 3
[0081] The difference from Example 1 is that step S1 is not performed.
[0082] Comparative Example 4
[0083] The difference from Example 1 is that step S2 is not performed.
[0084] Comparative Example 5
[0085] The difference from Example 1 is that step S3 is not performed.
[0086] Comparative Example 6
[0087] The difference from Example 1 is that in step S1, the mixed solution does not contain Al(NO3)3.
[0088] Comparative Example 7
[0089] The difference from Example 1 is that in step S1, the mixed solution does not contain H3BO3.
[0090] Comparative Example 8
[0091] The difference from Example 1 is that in step S2, the mixed gas does not contain NF3.
[0092] The cathode materials of Examples 1-3 and Comparative Examples 1-8, acetylene black and polyvinylidene fluoride (PVDF) binder are mixed uniformly in a mass ratio of 94:3:3, and then dispersed in N-methyl pyrrolidone (NMP) to obtain a paste-like mixture; the mixture is coated on an aluminum foil and dried at 90°C in a vacuum overnight to obtain a pole piece. The assembly of Li / LNMO button cells (model 2016) is carried out in a glove box filled with high-purity Ar: a metal lithium sheet is used as the negative electrode, a polypropylene film is used as the separator, 1 mol of LiPF6 is dissolved in ethyl carbonate / dimethyl carbonate (EC / DMC) (1:1, by volume) as the electrolyte, and the above pole piece is used as the positive electrode material of the battery.
[0093] The batteries assembled from Examples 1-3 and Comparative Examples 1-8 are tested for performance, and the test results are shown in Table 1:
[0094] Table 1 Performance test results of batteries assembled from Examples 1-3 and Comparative Examples 1-8
[0095]
[0096] As can be seen from the test results of Examples 1-3 in Table 1, as the thickness of the Li3BO3-LiAlO2 composite layer, the PAN-F conductive polymer layer and the g-C3N4 quantum dots increases, the conductivity and ion diffusion coefficient of the prepared positive electrode material rise, the Ni+Mn dissolution decreases, and the oxygen vacancy concentration decreases, thereby improving the discharge capacity, rate performance and cycle life of the material. As can be seen from Example 1 and Comparative Example 1, the performance indicators of Example 1 are all significantly better than those of Comparative Example 1, because the Li3BO3-LiAlO2 composite layer can improve the lithium ion diffusion rate and reduce the oxygen vacancy concentration; the PAN-F conductive polymer layer can block the penetration of the electrolyte and anchor the free Ni 2+ / Mn 2+ , reduce its dissolution concentration; and the g-C3N4 quantum dots can catalyze the decomposition of electrolyte by-products (such as ROCO2Li), thereby improving the electronic conductivity, and thus ultimately improving the energy density and cycle life of the material. As can be seen from Example 1 and Comparative Example 2, the performance of Comparative Example 2 is slightly lower than that of Example 1, and the difference is mainly in the electronic conductivity, transition metal dissolution and cycle performance, which indicates that the positive electrode material only coated with Li3BO3-LiAlO2 can only improve the lithium ion diffusion rate and oxygen vacancy concentration, but cannot significantly improve the electronic conductivity and transition metal dissolution. As can be seen from Example 1 and Comparative Example 3, the performance of Comparative Example 3 is slightly lower than that of Example 1, and the difference is mainly in the ion diffusion rate and cycle retention rate, because the PAN-F conductive polymer layer blocks the penetration of the electrolyte and anchors the free Ni 2+ / Mn 2+ , reduces its dissolution concentration, and the g-C3N4 quantum dots catalyze the decomposition of electrolyte by-products (such as ROCO2Li), thereby improving the electronic conductivity. As can be seen from Example 1 and Comparative Example 4, the performance of Comparative Example 4 is slightly lower than that of Example 1, and the difference is mainly in the transition metal dissolution and cycle retention rate, because the C-F bond in PAN-F has a high bond energy, which can significantly improve the oxidation resistance of the material at high voltage (such as ≥4.5V vs. Li + / Li), inhibit the decomposition of the electrolyte, and anchor the free Ni 2+ / Mn 2+ , reduce its dissolution concentration and reduce the interface side reaction. As can be seen from Example 1 and Comparative Example 5, the performance of Comparative Example 5 is slightly lower than that of Example 1, and the difference is mainly in the rate performance, because the g-C3N4 has a conjugated structure similar to that of graphene, which can provide an electron conduction path, and the nitrogen-containing functional groups can optimize the Li +In the interface diffusion dynamics, the charge transfer impedance (Rct) is reduced, thereby comprehensively improving the rate performance of the material. As can be seen from Example 1 and Comparative Example 6, the performance of Comparative Example 6 is slightly lower than that of Example 1, and the main difference is in the oxygen vacancy concentration, because LiAlO2 inhibits the generation of oxygen vacancies and reduces the surface oxygen vacancy concentration. As can be seen from Example 1 and Comparative Example 7, the performance of Comparative Example 7 is slightly lower than that of Example 1, and the main difference is in the ion diffusion coefficient, because Li3BO3 fills the grain boundary cracks and improves the lithium ion diffusion rate. As can be seen from Example 1 and Comparative Example 8, the performance of Comparative Example 8 is slightly lower than that of Example 1, and the difference between the two is that Example 1 uses F-copolymerized PAN for coating, and the C-F bond energy is high, which can significantly improve the oxidation resistance of the material at high voltage; the hydrophobic property after fluorination can reduce the erosion of water and HF to the positive electrode, and at the same time inhibit the dissolution of transition metal ions (such as / Mn 2+ , Ni 2+ ), thereby prolonging the cycle life.
Claims
1. A process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer, characterized in that: The following steps are involved: S1: In situ construction of Li3BO3-LiAlO2 composite layer: The LNMO precursor is immersed in a mixed solution of ethanol and water containing Al(NO3)3 and H3BO3, and stirred; ammonia is added dropwise to adjust the pH to 8.5-9.5 to generate Al(OH)3-B(OH)3 co-precipitate, which is centrifugally dried and annealed to form a Li3BO3-LiAlO2 composite layer on the LNMO precursor; S2: Deposition of PAN-F conductive polymer layer: The material obtained in step S1 is placed in a CVD reaction chamber, and a mixture of acrylonitrile and NF3 is introduced at 400-500°C for 1-3 hours to polymerize and form fluorinated polyacrylonitrile on the surface of the material; the obtained material is then treated with Ar plasma; S3: g-C3N4 quantum dot modification: g-C3N4 quantum dots are dispersed in an organic solvent, a surfactant is added, and ultrasonic treatment is performed to obtain a dispersion; the material obtained in step S2 is immersed in the above dispersion, stirred, and centrifuged to obtain a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer.
2. The process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer according to claim 1, wherein: In step S1, the D50 of the LNMO precursor is 200-300 nm.
3. The process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer according to claim 1, wherein: In step S1, in the mixed solution, the concentration of Al(NO3)3 is 0.2-0.4 mol / L, the concentration of H3BO3 is 0.1-0.2 mol / L, the volume ratio of ethanol and water is (3-5):1; the molar ratio of LNMO precursor, Al(NO3)3, and H3BO3 is 100:(2-4):(1-2).
4. The process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer according to claim 1, wherein: In step S1, the stirring temperature is 60-80° C., the stirring time is 4-8 h, and the ammonia water droplet addition rate is 1-2 mL / min.
5. The process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer according to claim 1, wherein: In step S1, the annealing temperature is 500-600° C., the heating rate is 2-5° C. / min, the annealing time is 3-6 hours, and the annealing is performed in an air atmosphere; the thickness of the formed Li 3 BO 3 -LiAlO 2 composite layer is 6-8 nm.
6. The process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer according to claim 1, wherein: In step S2, the volume ratio of acrylonitrile to NF3 in the mixed gas is (10-15):1; the power of the Ar plasma treatment is 100-150 W, and the time is 10-20 min; the thickness of the PAN-F conductive polymer layer is 2-3 nm.
7. The process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer according to claim 1, wherein: In step S3, the organic solvent is NMP and the surfactant is CTAB.
8. The process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer according to claim 1, wherein: In step S3, the concentration of g-C3N4 quantum dots in the dispersion is 0.5-1 mg / mL, and the concentration of the surfactant is 0.1-0.3 wt.%.
9. The process for preparing a high-voltage lithium nickel manganese oxide positive electrode material with a multi-level interface passivation layer according to claim 1, wherein: In step S3, the ultrasonic treatment time is 30-60 min; the stirring temperature is 60-80° C., and the stirring time is 6-8 h.
10. A high-voltage lithium nickel manganese oxide positive electrode material having a multi-level interface passivation layer prepared by the preparation process according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-performance all-solid-state lithium battery and preparation method thereof
CN111952673A
Preparation method of LiBO2 / LiAlO2 double-layer coated modified lithium ion battery quaternary positive electrode material
CN115196693A